Пародонтопротекторное действие антидисбиотических средств при экспериментальном сахарном диабете 2 типа = Periodontitis-protective effecr of anti-dysbiotic means at experimental diabetes mellitus type 2 - Stupak, E. P.; Skidan, K. V.; Skidan, M. I.; Dem'yanenko, S. A. (Journal of Education, Health and Sport, 2015)
Stupak E. P., Skidan K. V., Skidan M. I., Dem'yanenko S. A. Пародонтопротекторное действие антидисбиотических средств при экспериментальном сахарном диабете 2 типа = Periodontitis-protective effecr of anti-dysbiotic means at experimental diabetes mellitus type 2. Journal of Education, Health and Sport. 2015;5(12):588-597. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44264 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A588-597 http://pbn.nauka.gov.pl/works/687233 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. УДК 616.731-07.23.008 ПАРОДОНТОПРОТЕКТОРНОЕ ДЕЙСТВИЕ АНТИДИСБИОТИЧЕСКИХ СРЕДСТВ ПРИ ЭКСПЕРИМЕНТАЛЬНОМ САХАРНОМ ДИАБЕТЕ 2 ТИПА PERIODONTITIS-PROTECTIVE EFFECR OF ANTI-DYSBIOTIC MEANS AT EXPERIMENTAL DIABETES MELLITUS TYPE 2 Е. П. Ступак1, К. В. Скидан2, М. И. Скидан2, С. А. Демьяненко3 E. P. Stupak1, K. V. Skidan2, M. I. Skidan2, S. A. Dem'yanenko3 1ВГУУ «Украинская медицинская стоматологическая академия», г. Полтава 2Харьковский национальный медицинский университет 3Крымский государственный медицинский университет им. С. И. Георгиевского, г. Симферополь 1HSEI «Ukrainian medical Stomatological Academy», Poltava 2Kharkiv national medical university, Kharkiv 3Crimean State Medical University named after S.I.Georgievskij, Simferopol Abstract Aim: To determine the therapeutic and preventive effect of oral gels with anti-dysbiotic means (ADM) on periodont at type 2 diabetes mellitus (DMT2). Materials and Methods: Diabetes in rats was induced by an intra-muscular administration of protamine sulfate for 10 days. As ADM there were used lysozyme, quercetin, flour, mucosin and flour from vine leaves, which were applied in form of gels on the oral mucosa of rats for 2 weeks. In the gums' homogenates there were determined the activities of urease, lysozyme, elastase, catalase and the MDA content. The degree of dysbiosis by Levitsky was calculated as the ratio of the relative activities of urease and lysozyme. The antioxidant-prooxidant index API was calculated as the ratio of the catalase activity and the MDA content. Results: The urease activity, the degree of dysbiosis, the elastase activity and the MDA content were increased while the lysozyme activity and the index API were reduced in rats with diabetes type 2 in the periodont. Applied gels containing ADM showed therapeutic and preventive effects. Conclusion: At diabetes type 2 in the periodont of rats there were developing dysbiosis and inflammation. The application of oral gels with ADM provided a therapeutic and preventive treatment. Keywords: diabetes type 2, periodont, dysbiosis, inflammation, anti-dysbiotic means, oral gels. Резюме При экспериментальном сахарном диабете 2 типа в десне развивается дисбиоз и воспаление. Оральные гели с антидисбиотическими средствами (лизоцим, кверцетин, мукозин и мука из виноградных листьев) оказывают лечебно-профилактический эффект. Ключевые слова: сахарный диабет 2 типа, пародонт, дисбиоз, воспаление, антидисбиотические средства, оральные гели.